Analysis Of Inhibiting Factors For The Effectiveness Of Public Information Policy In The Services Of BPJS During The Covid-19 Pandemic At Puskesmas Kartini, Pematang Siantar City - Ivan Elisabeth Purba; Parlindungan Purba; Rahmat Alyakin Dakhi (UIN Sumatera Utara, 2022)
BPJS Health is a legal entity that was established in order to organize a health insurance program. The problem with the BPJS program to ensure public health is that people complain that the health services they receive at both the hospital and the puskesmas are not in accordance with program procedures, such as being treated with potluck and queues. Because there are still problems felt by the community, the health services provided are ineffective. As a result, the purpose of this research is to determine and describe the efficacy of the BPJS Health program in health services at the Kartini Health Center in Pematangsiantar City. The research method used in this study is a literature review. Data collection techniques include observing and documenting documents related to the BPJS health program's implementation. According to the study's findings, there are factors impeding the effectiveness of the BPJS Health Program in Health Services that have not been effective because there are still complaints from the community and the community is also not fully aware of the existence of the BPJS Health program to help the community, particularly the underprivileged. The interactions between the three components of program implementation (programs, beneficiaries, and organization) have not gone well, and the output has not met expectations.